TRANSFORMING CARBON EMISSION TRANSPARENCY: THE IMPACT OF GREEN R&D, MEDIA EXPOSURE, AND ENVIRONMENTAL COSTS IN INDONESIA - Majidah, Rona; Octary, Ayu Dwiny; Fathia, Syaharani Noer (Jurnal Akuntansi dan Keuangan (JAK), 2025)
In supporting global carbon emission reduction initiatives, the Financial Services Authority (OJK) has taken part in organizing a carbon exchange aimed at reducing carbon emission levels. Additionally, the Indonesian Government enacted Law Number 16 of 2016 concerning the Ratification of the Paris Agreement to the United Nations Framework Convention on Climate Change, as well as Presidential Regulation Number 61 of 2011 concerning the national action plan for reducing greenhouse gas emissions. Therefore, companies must implement an effective environmental management system, which includes pollution prevention, the reuse or recycling of waste and unused products, energy efficiency by seeking alternative renewable energy sources, and regulation. This study aims to investigate the effects of R&D intensity, media exposure, and environmental cost allocation on the quality of carbon emission disclosure. Carbon emission disclosure is measured using a scoring index developed by Choi et al. (2013) based on the Carbon Disclosure Project (CDP). The study’s results show that environmental costs and media exposure have a positive and significant effect on carbon emission disclosure in Indonesia, while R&D intensity has a positive but insignificant effect. In Indonesia, factors such as environmental budgets and media exposure play a crucial role in encouraging companies to be more transparent about their carbon emissions. Regarding R&D intensity, although it fosters corporate innovation, it has not yet significantly driven companies to be more open about their carbon emissions at this time.